2007
DOI: 10.1159/000108306
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of cancer chromosomes and genomes

Abstract: A key feature of cancer chromosomes and genomes is their high level of dynamics and the ability to constantly evolve. This unique characteristic forms the basis of genetic heterogeneity necessary for cancer formation, which presents major obstacles to current cancer diagnosis and treatment. It has been difficult to integrate such dynamics into traditional models of cancer progression. In this conceptual piece, we briefly discuss some of the recent exciting progress in the field of cancer genomics and genome re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 119 publications
1
86
0
1
Order By: Relevance
“…At the chromosomal level, many authors have described that two well established chromosomal profiles may be generated by the karyotypic evolution process: the first one with a high frequency of CCAs, a pattern which provides growth advantage, and the second one characterized by a high frequency of NCCAs, a pattern which provides survival advantage (Albertson et al 2003;Heng et al 2006c;Bayani et al 2007;Ye et al 2007). Comparison of DT and NDI values showed that UW402 cells have higher proliferative capacity than UW473 cells (DT UW402 \ D-T UW473 and NDI UW402 [ NDI UW473 ), on the other hand, UW402 had significantly less capacity to form colonies than UW473.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the chromosomal level, many authors have described that two well established chromosomal profiles may be generated by the karyotypic evolution process: the first one with a high frequency of CCAs, a pattern which provides growth advantage, and the second one characterized by a high frequency of NCCAs, a pattern which provides survival advantage (Albertson et al 2003;Heng et al 2006c;Bayani et al 2007;Ye et al 2007). Comparison of DT and NDI values showed that UW402 cells have higher proliferative capacity than UW473 cells (DT UW402 \ D-T UW473 and NDI UW402 [ NDI UW473 ), on the other hand, UW402 had significantly less capacity to form colonies than UW473.…”
Section: Discussionmentioning
confidence: 99%
“…It is represented by clonal (CCA) and nonclonal (NCCA) chromosomal alterations, essential elements for evolution and development of cancer, driving critical events as growth and survival advantages and karyotypic evolution (Heng et al 2006a, b;Shaffer and Tommerup 2005). Moreover, since this model could be applied from transition to metastatic disease and in treatment resistance evaluation, it has been recently suggested the integration of monitoring of both NCCAs and CCAs into the standard practice of clinical cytogenetic reporting (Heng et al 2006b(Heng et al , 2010Ye et al 2007;Bayani et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, various karyotypes represent different genome context defined systems. 28 The same gene mutation likely has distinctive functions in different systems. As such, other factors apart from K-Ras status largely contribute to the lack of correlation between Ras and signaling events downstream and will require further study to elucidate.…”
Section: Discussionmentioning
confidence: 99%
“…If genome-wide association studies are to be applied to types C and D, the use of smaller, homogenous subpopulations will be key. Notably, an observation that is often ignored in common diseases is that abnormal genomes often present in mosaic and not in clonal form 5,6 .…”
Section: Competing Interests Statementmentioning
confidence: 99%
“…Finally, several common diseases, including autism and Alzheimer's disease, are associated with altered karyotypes 5,6 . This observation suggests similarities in the bases of common disease and cancer 7 , which arise from stochastic genome alterations rather than common gene mutations 8,9 .…”
mentioning
confidence: 99%